HUBUNGAN PERAN DAN FUNGSI KEPALA RUANGAN DENGAN KUALITAS HANDOVER PASIEN DI RUANG RAWAT INAP RS TK.II ROBERT WOLTER MONGISIDI - Norman Alfiat Talibo; Irma M. Yahya; Sherin D. Boda (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2022)
Patient safety is a basic thing in the quality of health and nursing services. During the handover process, a nurse must be as effective as possible, as clearly as possible, as short as possible and as comprehensively as possible regarding nurses' independent and collaborative actions. The purpose of this study was to determine the relationship between the role and function of the head of the room with the quality of handovers at Tk.II Robert Wolter Mongisidi Hospital Manado. This research method uses descriptive analytic with a cross sectional approach where the independent and dependent variables are studied simultaneously. The sample of respondents as many as 32 people using random sampling. Data collection using a questionnaire sheet. Analyzed with Chi Square ? 0.05 statistical test. The results of the study obtained p value = 0.036, where p value = 0.000, which is smaller than = 0.05, meaning that the alternative hypothesis (Ha) is accepted or there is a relationship between the role and the quality of handovers at Tk.II Robert Wolter Mongisidi Hospital Manado. p value = 0.000 where p value = 0.000 which is smaller than = 0.05 meaning that the alternative hypothesis (Ha) is accepted or there is a relationship between function and handover quality at Tk.II Robert Wolter Mongisidi Hospital Manado The conclusion of this study is that there is a relationship between the role and function of the head of the room with the quality of handover at the Tk.II Robert Wolter Mongisidi Hospital, Manado. Suggestions from the results of this study can be used as input for hospital considerations that are used to improve health services and design nursing service policies in terms of patient handover by conducting ongoing education or training so that the level of knowledge and nursing actions becomes better.